Network of Hadith of Madurese Scholars: Genealogy, Diffusion, and Intellectual Treasures of Hadith - Mohammad Subhan Zamzami; Achmad Fauzi (Dialogia, 2022)
Hadith is a field of science that is less desirable, so the study of hadith and research on hadith in Indonesia, including in Madura, is far behind other fields of Islamic sciences. Whereas hadith is the mother of Islamic science and should be the main object of study. So far, various pesantren in Madura is more identical to Arabic, interpretation, and fiqh, so research on pesantren, including pesantren in Madura, is dominated by research on these three fields of study. This type of research is descriptive research with a hadith approach through library research and field research to describe the network of hadith scholars in Madura. This study shows that in general, the network of hadith scholars in Madura cannot be separated from the network of hadith scholars in Indonesia which originates from the network of Middle Eastern scholars, especially Mecca from the late 19th to 21st centuries, which was formed and spread through teacher-student relationships and friendships. They contributed to the development of hadith studies in Indonesia through the study of hadith books, sharing of records and ijazah sanad hadith, and writing and publishing work in the field of hadith.